Advances in Computational Fluid Dynamics Applied to the Greenhouse Environment - Flores-Velázquez, Jorge; Torre-Gea, Guillermo De la; Rico-García, Enrique; López-Cruz, Irineo L.; Rojano-Aguilar, Abraham (IntechOpen, 2012)
None